THE EFFECT OF ECONOMIC VALUE ADDED, AND MARKET VALUE ADDED ON STOCK RETURNS WITH DIVIDEND POLICY AS A MODERATION VARIABLE - Aditya Rizkia Dwi Saputra; Sugiyanto; Holiawati (ZILLZELL MEDIA PRIMA, 2026)
This study aims to obtain empirical evidence regarding the influence of economic value added and market value added on stock returns, with dividend policy as a moderating variable. This study uses an associative quantitative approach with a purposive sampling method, resulting in a sample of 21 companies with a total of 105 observation data for the 2020–2024 period. The research data are sourced from financial reports obtained through the official website of the Indonesia Stock Exchange and the websites of each company. Data analysis was conducted using panel data regression with the help of E-Views 13, where the first equation model uses the Command Effect Model. The results show that economic value added has an effect on stock returns, and market value added has no effect on stock returns. In addition, dividend policy is proven to moderate the relationship between EVA and MVA on stock returns.